History of teachers´ training in Paraguay (Praxis Educativa, 2015)
The analysis of the teachers’ training process, in the frame of an analytical perspective, highlights outstanding aspects of its evolution. Even when the interest is focused on formation, a more general vision is kept to achieve a more global perception of characteristics and changes experienced in certain aspects and levels of its organization. It aims at grasping singularities of certain historical moments, seen as a socio-cultural reality which ensembles upon specific relations and special assessing contents. Through data analysis it is feasible to detect relations in the educational sphere and socioeconomic and cultural contexts prevailing in a certain historical juncture which is the passive reflection of the contextual reality, and an active element that recognizes a certain structural autonomy and, consequently, an effective change factor in teachers’ training.
Keywords: teachers’ training; state; educational system; innovations